The Role of the Family in Preventing Underage Marriage: An Islamic Legal Perspective - Putra, Rido Saprinaldo; Sulastri, Widia; Aryanti, Yosi (Samara: Journal of Islamic Law and Family Studies, 2025)
The family is one of the important factors in preventing underage marriage. Families have a role to play in educating and guiding children about the importance of marriage in accordance with Islamic law. The purpose of this study is to describe the role of families in preventing underage marriage from the perspective of Islamic law in Sungai Liku. In discussing this research, the author uses field research with a descriptive method to describe how families play a role in preventing underage marriage in Nagari Sungai Liku Pelangai Pesisir Selatan. In this study, the author uses a legal approach, namely an empirical juridical or sociological juridical approach. The factors that can influence the role of the family in preventing underage marriage in Sungai Liku Pelangai are that the role of the family can influence a child's decision to marry underage in Sungai Liku Pelangai, where effective collaboration between all these elements can compensate for the lack of parental education in preventing underage marriage. The role of the family can be carried out by providing an understanding of the negative impacts of underage marriage, monitoring and supervising children's social interactions, and empowering children. The Liku Pelangai River, where parents set an example in practicing religion, such as praying Maghrib in congregation and reciting the Quran together at the mosque. Encouraging children to recite the Quran at the mosque, pray Maghrib in congregation, and participate in monitoring their children's interactions with their peers. Then families can create an open environment within the family, inviting children to talk about their future, school, and daily social interactions.